2017
DOI: 10.1007/s10278-016-9940-7
|View full text |Cite
|
Sign up to set email alerts
|

Value-Based Assessment of Radiology Reporting Using Radiologist-Referring Physician Two-Way Feedback System—a Design Thinking-Based Approach

Abstract: In the era of value-based healthcare, many aspects of medical care are being measured and assessed to improve quality and reduce costs. Radiology adds enormously to health care costs and is under pressure to adopt a more efficient system that incorporates essential metrics to assess its value and impact on outcomes. Most current systems tie radiologists' incentives and evaluations to RVU-based productivity metrics and peer-review-based quality metrics. In a new potential model, a radiologist's performance will… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The anatomical structure of orthopedics is complex, and it is difficult to convert a 2D image into a 3D model with only spatial imagination [ 6 ]. Shaikh et al used AR/VR technology to build a 3D visual surgery education model, convert patient image data into holographic images, and import them into VR equipment, where teachers and students wear HoloLens at the same time [ 7 ]. Eladl et al asked 16 surgeons to complete a series of actions such as standard nail transfer in the traditional CT-guided and VR-assisted laparoscopic trainer and found that the operation time, accuracy, and stability of the VR-assisted group were better than those of the CT-guided group, and the more complex the operation, the greater the difference of results [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The anatomical structure of orthopedics is complex, and it is difficult to convert a 2D image into a 3D model with only spatial imagination [ 6 ]. Shaikh et al used AR/VR technology to build a 3D visual surgery education model, convert patient image data into holographic images, and import them into VR equipment, where teachers and students wear HoloLens at the same time [ 7 ]. Eladl et al asked 16 surgeons to complete a series of actions such as standard nail transfer in the traditional CT-guided and VR-assisted laparoscopic trainer and found that the operation time, accuracy, and stability of the VR-assisted group were better than those of the CT-guided group, and the more complex the operation, the greater the difference of results [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, and taking into account the opinions expressed by an interviewee from Group D and an interviewee from Group B, the metric ‘percentage of cases in which the consultation between the radiologist and the requesting doctor has an impact on the elaboration or alteration’ was reformulated, and it was considered relevant to add the metric. These metrics referring to the impact of the report are considered as an intermediate outcome, possibly measurable through a feedback system aimed at requesting physicians (Shaikh et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Some sites have tested "patient friendly," educational report descriptions of significant findings launched out of hyperlinks [62]. Hyperlinks also can launch quality improvement feedback mechanisms for downstream physicians [63][64][65].…”
Section: Current Statementioning
confidence: 99%